Contra Graecum: Bilingual Observations from 1 Corinthians - Kreinecker, Christina M. (New Testament studies, 2025)
Contra graecum, against the Greek, is a term used in the critical apparatus of the so-called Oxford Vulgate to indicate passages where individual manuscripts, early Christian authors or the entire Latin tradition present a text that differs from the Greek witnesses. This contribution discusses three ex-amples from 1 Corinthians (1 Cor 7.33-4, 15.5, 14.11). At 1 Cor 7.33-4, verse divisions have varied ever since the first printed New Testament with modern verse numbers (Estienne 1551). This is partly due to the different interpretations of the verb μεμέρισται either as masculine or feminine. The difference is discussed already in early Christian authors, with Jerome finding meaning in both despite a preference for the masculine form. In 1 Cor 15.5, the number of people to whom Christ appeared differs, with ‘twelve’ in Greek and ‘eleven’ in Latin. Only a few Greek witnesses read ‘eleven’, including bilingual codices (Claromontanus, Boernerianus and Augiensis). Again, the difference was discussed already by early Christian authors, with Augustine finding meaning in both numbers. In 1 Cor 14.11, the Greek text identifies both the speaker and the listener as unintelligible ‘barbarians’ to each other. In contrast, the Latin text refers to two speakers, thus interpreting the passage strictly in the context of speaking in tongues (1 Cor 14.9, 13). The three examples from 1 Corinthians illustrate the main challenges of New Testament textual criticism, including those of contamination, coincidence of readings, incomplete transmission, and, in the case of bilingual manuscripts, mutual influence of readings.